New Insight into the Photochromism of Spiropyrans: Substituent Effects on Equilibrium, Rate Constants, and Dipole Moments - Hermes, Niklas; Vogt, Mascha Sirin; Gruber, Vanessa; Maier, Rebecca F.; Niazkar, Kimia; Giernoth, Ralf Wolfgang (Synthesis, 2025)
Spiropyrans (SPs) and merocyanines (MCs) are among the most widely used photochromic systems today. Besides solvent polarity and temperature, the electronic properties of the substituents have a significant influence on photochromic behavior. In this work, a comprehensive study on the influences of electron-donating and -withdrawing substituents at the benzopyran as well as the indole moiety of the photochromic system are elucidated. For this purpose, changes in rate constants and the shift of the SP/MC equilibrium are investigated utilizing UV/vis and NMR spectroscopy. Based on DFT calculations, a relationship between these properties and the dipole moments of the molecules is established.
Keywords: Spiropyran; Merocyanine; Photochromism; Substituent-effects; Rate constant; Dipole moment